Kajian Yuridis Terhadap Wanprestasi Perjanjian Utang Piutang - Achmad Nur Miftahuddin; Kairuddin Karim (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2023)
This study aims to find out the process of resolving default cases in debt and credit agreements and also to find out the legal considerations of judges in passing decisions on default cases in debt and credit agreements, especially in case Number 6/Pdt.G.S/2019/PN.Pre. This research uses a normative research type supported by statutory and case study approaches. The types and sources of data using primary, secondary, tertiary, and data analysis are studied qualitatively and descriptively. The research results show that in resolving this default case, all stages have been carried out and implemented. In this case, the judge has sought peace between the Plaintiff and the Defendant including advising the parties to make peace outside the court (mediation) this effort was not achieved, and the judge's legal considerations in deciding the case at the District Court of Parepare City Number 6/Pdt. G.S/2019/PN.Pre is correct and correct, in which the Defendants must pay off immediately and unconditionally all of the Defendants' credit arrears as required and agreed in the Defendants' Debt Acknowledgment Letter.